Microplastics and their impact on the marine environment - Abhay Pandey (Sampreshan, ISSN:2347-2979 UGC CARE Group 1, 2024)
Microplastics are tiny plastic particles less than five millimeters in diameter that are increasingly polluting the world's oceans. This research paper will explore the sources and types of microplastics, their impact on marine organisms, and potential solutions to mitigate microplastic pollution.